Flow paths and phosphorus transfer pathways in two agricultural streams with contrasting flow controls. Issue 16 (8th January 2015) - Mellander, Per‐Erik; Jordan, Phil; Shore, Mairead; Melland, Alice R.; Shortle, Ger; Bishop, Kevin; Seibert, Jan
Abstract In this paper, we analyse 4 years of data from simultaneous high‐frequency monitoring of streamflow and phosphorus (P) concentration. This was carried out to investigate hydrological flow paths and P transfer pathways from diffuse sources in two intensively farmed river catchments (~10 km2) with contrasting flow controls and dominating flow paths. Catchment scale P loss was viewed on an annual and event flow basis and related to hydrological flow paths. A grassland catchment with mostly poorly drained soils, and a higher Q10:Q90 ratio (60 compared with 24), had three times higher annual P loss than an arable catchment with mostly well‐drained soils (1.04 compared with 0.34 kg TP ha−1) despite the arable catchment having larger areas with high soil P status and more discharge. Neither of the catchments indicated supply limitations. The magnitude of the P losses from the two catchments was not defined by land use, source pressure or discharge volume but rather by more basic rainfall‐to‐runoff partitioning influences that determine proportions of quickflow and slowflow. There were larger differences between the years than between the catchments, and the P loss of the arable catchment appeared more sensitive to climate. The results confirmed the need to manage the quickflow components of runoff to moderate P transfers. Therefore, in order to further reduce diffuse pollution it may be necessary to account for the contrast in hydrological function before or in addition to any of the other factors known to influence P losses from catchments (such as soil P and land use). Schemes designed to attenuate diffuse P after mobilization from soil surfaces can then be targeted (and resourced) more effectively. Copyright © 2014 John Wiley & Sons, Ltd.